2014
DOI: 10.1530/rep-13-0376
|View full text |Cite
|
Sign up to set email alerts
|

Maternal dietary omega-3 fatty acids and placental function

Abstract: The developing fetus requires substantial amounts of fatty acids to support rapid cellular growth and activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(91 citation statements)
references
References 78 publications
(76 reference statements)
4
86
1
Order By: Relevance
“…This contrasts with our finding that maternal EPA levels increased by w300%, whereas maternal DHA levels were only increased by w65% in the n-3 PUFA group (Barden et al 2006). This suggests that placental EPA levels may be regulated independently of maternal levels, reflecting differences in placental uptake, accumulation or transfer of the two n-3 PUFAs (Jones et al 2014). Consistent with this view, we have recently shown that in rats, placental levels of EPA and DHA at term were increased as a result of n-3 PUFA supplementation by approximately two-and fourfold, respectively, compared with maternal levels which increased by 16-and threefold respectively (Jones et al 2013a).…”
Section: Discussioncontrasting
confidence: 99%
“…This contrasts with our finding that maternal EPA levels increased by w300%, whereas maternal DHA levels were only increased by w65% in the n-3 PUFA group (Barden et al 2006). This suggests that placental EPA levels may be regulated independently of maternal levels, reflecting differences in placental uptake, accumulation or transfer of the two n-3 PUFAs (Jones et al 2014). Consistent with this view, we have recently shown that in rats, placental levels of EPA and DHA at term were increased as a result of n-3 PUFA supplementation by approximately two-and fourfold, respectively, compared with maternal levels which increased by 16-and threefold respectively (Jones et al 2013a).…”
Section: Discussioncontrasting
confidence: 99%
“…IUGR involves not only inadequate nutrient supply but also reduced oxygenation, which causes hypoxia that increases oxidative stress and triggers low-grade inflammation [11]. The antioxidant defense system in IUGR fetuses is weakened, exacerbating oxidative stress [1214], which in turn aggravates the effects of IUGR [15]. Previous studies in sheep have shown that the deleterious effects of oxidative status at the fetoplacental unit may be prevented by the administration of antioxidant agents (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…EPA, DPA, and DHA are usually referred to as n-3 long-chain PUFA (n-3 LCPUFA). A source of these long-chain fatty acids is required during pregnancy for fetal and placental development (reviewed by Mennitti et al 2015;Jones et al 2014). Maternal intake/status of n-3 LCPUFA during pregnancy and lactation has been found to positively impact maternal, infant, and child health in many systematic reviews (Yang et al 2013;Imhoff-Kunsch et al 2012;Larqué et al 2012;Horvath et al 2007).…”
Section: Introductionmentioning
confidence: 99%